1992
DOI: 10.1002/1097-0142(19921015)70:8<2192::aid-cncr2820700830>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stress impairs natural killer cell programming of tumor for lysis in patients with sarcomas and other solid tumors

Abstract: Background. Natural killer (NK) cells may provide a first line of defense against the metastatic implantation of circulating tumor emboli. Because tumor emboli are discharged systemically in patients undergoing solid tumor resection, it is important to determine the nature of surgical‐stress impairment of perioperative NK cell cytotoxic function. Methods. The authors studied 85 patients undergoing surgical resection of solid tumors, most of whom had an abrupt and marked decrease in NK cell cytotoxicity that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 25 publications
3
41
1
2
Order By: Relevance
“…Specifically, we suggest that a mechanism contributing to the promotion of metastasis by surgery is an adrenergic suppression of NK activity. Indeed, suppression of NKA is well documented clinically following surgery (Pollock et al, 1992;Beitsch et al, 1994;Shirakawa et al, 1998), has been suggested by animal and human studies to promote metastasis (Brittenden et al, 1996;Ben-Eliyahu et al, 1999), and is shown here and in our study in women to be modulated by the oestrous and menstrual cycles.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, we suggest that a mechanism contributing to the promotion of metastasis by surgery is an adrenergic suppression of NK activity. Indeed, suppression of NKA is well documented clinically following surgery (Pollock et al, 1992;Beitsch et al, 1994;Shirakawa et al, 1998), has been suggested by animal and human studies to promote metastasis (Brittenden et al, 1996;Ben-Eliyahu et al, 1999), and is shown here and in our study in women to be modulated by the oestrous and menstrual cycles.…”
Section: Discussionsupporting
confidence: 78%
“…Second, immune suppression induced by surgical stress could render the organism susceptible to metastatic development that would otherwise have been kept under control. Indeed, marked suppression of NKA following surgical intervention is clinically well documented (Pollock et al, 1992;Beitsch et al, 1994;Brittenden et al, 1996;Shirakawa et al, 1998), and we have recently shown that such suppression in rats markedly promotes metastatic development (Ben-Eliyahu et al, 1999). Several studies have implicated sympathetic activation in suppressing NKA (Irwin et al, 1990;Brenner et al, 1992;Wu and Pruett, 1996;Ben-Eliyahu and Shakhar, 2000).…”
mentioning
confidence: 71%
“…Owing to its ability to seal vessels, it is possible that laser thermotherapy gives less intravascular tumour cell spread than surgical resection. Surgery has been shown to cause generalized immunosuppression, including depressed function of immune cells, such as lymphocytes, NK cells and non-parenchymal cells of the liver, which have the capacity to kill tumour cells (Pearson et al, 1986;Pollock et al, 1987Pollock et al, , 1992Colachio et al, 1994;Oka et al, 1994). Surgical resection also induces the production and release of growth factors, events that may stimulate cell division of tumours and facilitate recurrence and spread (Goustin et al, 1986;Fisher et al, 1989;Davies et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These unwanted effects of surgery may be caused, at least partly, by immunosuppression and by the release of growth factors involved in tissue healing (Eggermont et al, 1987;Loizidou et al, 1991;Panis et al, 1992;Pollock et al, 1992;Dingemans et al, 1993;Oka et al, 1994;Slooter et al, 1995). One of the advantages of local tissue destruction is that the trauma is small compared with surgery.…”
mentioning
confidence: 99%
“…The exact mechanisms are unknown, but there is solid evidence for the impairment of natural killer (NK) cell and T cell function in response to acute and chronic psychological stress. Surgery also has been associated with impaired immunity in the immediate postoperative period, an effect that is compounded by the use of adjuvant chemotherapy and radiation, which have short-term effects on the generation and activity of immune effectors [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%